THE IMPACT OF CORPORATE GOVERNANCE AND SUSTAINABILITY PERFORMANCE ON FIRM VALUE: EVIDENCE FROM ENERGY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Yusuf; Danang Choirul Umam (International Journal Management and Economic, 2026)
This study investigates the impact of corporate governance mechanisms and sustainability performance on firm value in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. Using balanced panel data and employing a Fixed Effects Model, the analysis examines the roles of board independence, board size, audit committee, institutional ownership, sustainability performance, and firm size in explaining firm value. The results show that independent commissioners have a positive and significant effect on firm value, indicating that effective board independence enhances monitoring quality and investor confidence. Other governance attributes and sustainability performance do not exhibit significant effects, suggesting that formal governance structures and sustainability initiatives are not immediately reflected in market valuation. The overall model is statistically significant and explains a moderate proportion of the variation in firm value. These findings imply that investors in the energy sector prioritize governance quality over structural compliance and short-term sustainability disclosures. The study provides empirical evidence on the relevance of corporate governance in shaping firm value within a capital-intensive and environmentally sensitive industry context.